Sistem Informasi Perpustakan Berbasis Web Pada Sd 028303 Binjai Barat - Ramadhana Hambi; Arpan (CV. Hawari, 2025)
School libraries play an important role in supporting the learning process, especially at the elementary school level. As a learning resource center, the library provides a variety of reading materials that support the learning activities of both students and teachers. However, library management that is still carried out manually—such as recording book loans and returns using logbooks—often causes several problems, including recording errors, delays in data searches, and difficulties in report preparation. This condition requires a technology-based solution that can improve the efficiency and accuracy of library data management. This study aims to design and develop a web-based library information system to be used at SD Negeri 028303 Binjai Barat. The development method used is the prototyping model, which allows users to provide direct feedback on the early version (prototype) of the system being developed. This method was chosen to ensure the system truly aligns with users' needs in the field. The system includes key features such as user login, book data management, member data management, loan and return transactions, as well as automated transaction reporting. The implementation results show that the system functions well as expected. It is capable of speeding up library services, minimizing recording errors, and providing convenience for staff and students in accessing information. Therefore, the implementation of this web-based library information system can significantly improve the quality of library services and support a more effective teaching and learning process at SD Negeri 028303 Binjai Barat.